Anthropological Expertise and Legal Practice: In Conversation - Foblets, Marie-Claire; Sapignoli, Maria; Donahoe, Brian (Law and Anthropology, 2024)
This book draws on concrete cases of collaboration between anthropologists and legal practitioners to critically assess the use of anthropological expertise in a variety of legal contexts from the point of view of the anthropologist as well as of the decision-maker or legal practitioner. The contributions, several of which are co-authored by anthropologist–legal practitioner tandems, deal with the roles of and relationships between anthropologists and legal professionals, which are often collaborative, interdisciplinary, and complementary. Such interactions go far beyond courts and litigation into areas of law that might be called ‘social justice activism’. They also entail close collaboration with the people –often subjects of violence and dispossession –with whom the anthropologists and legal practitioners are working. The aim of this collection is to draw on past experiences to come up with practical methodological suggestions for facilitating this interaction and collaboration and for enhancing the efficacy of the use of anthropological expertise in legal contexts. Explicitly designed to bridge the gap between theory and practice, and between scholarship and practical application, the book will appeal to scholars and researchers engaged in anthropology, legal anthropology, socio-legal studies, and asylum and migration law. It will also be of interest to legal practitioners and applied social scientists, who can glean valuable lessons regarding the challenges and rewards of genuine collaboration between legal practitioners and social scientists. : The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons [Attribution-Non Commercial-No Derivatives (CC BY-NC-ND)] 4.0 license.